The Outstanding School Library Management (A Site Study at SDN Kalibanteng Kidul 1, Official Technical Implementation Unit of Education, Semarang Barat, Semarang) - Sulaini, Sri (2012)
The objectives of this research are to describe (1) the characteristic of the outstanding school's library management plan at SDN Kalibanteng Kidul 01 Semarang, (2) the characteristic of the outstanding school's library design at SDN Kalibanteng Kidul 01 Semarang, (3) the characteristic of the result of the outstanding school's library design at SDN Kalibanteng Kidul 01 Semarang. It is a qualitative research and ethnography design which is conducted at SDN Kalibanteng Kidul 1 Semarang. The informants of this research are the library administrator, librarians, and students of SDN Kalibanteng Kidul 1 Semarang. The data sources are event, document, informant, and artifact. Techniques used in data collection are in-depth interview, documentation and observation. Data analysis of this research are data collection, data reduction, data display, and taking conclusion. Data validity in this research included credibility, transferability, dependability, and conformability. The results of this research are three (1) the school library management plan activity is started with a meeting held by the principal, teachers, and school committee. The meeting also discusses the school vision and mission in the formation of the school library. In the library management plan also discusses about the external and internal environment of the school library. The internal environment of the library includes the formation of the organizational structure, staff, collection, access, building, budget and technical service. The external environment includes the environment of the school. School library management plan is doing SWOT analysis (strength, weakness, opportunities, and threats). The last phase in the school library management plan is by implementing all activities planned before. (2) The library building has been tailored to the number of students and the existing regulation, namely 56 m2. Facilities which are available in the school library of SDN Kalibanteng Kidul 1 Semarang are table, chairs, Air Conditioner, library collections, and a laptop. (3) The facilities in the library of SDN Kalibanteng Kidul 1 Semarang is arranged well. With the Air Conditioner in the library can attract users to come to the library. The long table has a bulkhead to make the privacy of users is not disturbed each other. The policy of the library officer giving the carpet due to be one way to make the library can accommodate more students. The books collection arrangement with DDC classification system is very helpful to users who will search for the reference.